2015
DOI: 10.1007/s00430-015-0395-0
|View full text |Cite
|
Sign up to set email alerts
|

Superresolution imaging of viral protein trafficking

Abstract: The endoplasmic reticulum (ER) membrane is closely apposed to the outer mitochondrial membrane (OMM), which facilitates communication between these organelles. These contacts, known as mitochondria-associated membranes (MAM), facilitate calcium signaling, lipid transfer, as well as antiviral and stress responses. How cellular proteins traffic to the MAM, are distributed therein, and interact with ER and mitochondrial proteins are subject of great interest. The human cytomegalovirus UL37 exon 1 protein or viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 99 publications
(163 reference statements)
2
16
0
Order By: Relevance
“…Using superresolution imaging by multifocal structured illumination microscopy (MSIM), gated stimulated emission depletion (gSTED) and photoactivated localization microscopy (PALM), we established that vMIA forms clusters of ~100–150 nm at the OMM of human cells 13,36 . Clustering has also been reported for inner mitochondrial membrane (IMM) proteins including mitochondrial inner membrane or cristae organizing system (MICOS or MINOS), and cytochrome C oxidase subunit 2 of complex IV 35,37 .…”
Section: Introductionmentioning
confidence: 99%
“…Using superresolution imaging by multifocal structured illumination microscopy (MSIM), gated stimulated emission depletion (gSTED) and photoactivated localization microscopy (PALM), we established that vMIA forms clusters of ~100–150 nm at the OMM of human cells 13,36 . Clustering has also been reported for inner mitochondrial membrane (IMM) proteins including mitochondrial inner membrane or cristae organizing system (MICOS or MINOS), and cytochrome C oxidase subunit 2 of complex IV 35,37 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that HCMV UL37 proteins traffic sequentially from the ER into the mitochondrial outer membrane (Bhuvanendran et al, 2014; Colberg-Poley et al, 2015; Mavinakere et al, 2006). Characterization of the subcellular localization and trafficking of HCMV UL37 proteins required establishing a protocol in which ER and mitochondria could be reliably separated from one another, despite their prevalent interconnection.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning viral infections, several viral proteins were shown to localize to MAM (for reviews, see Williamson & Colberg-Poley 2009, Colberg-Poley et al 2015, de Armas-Rillo et al 2016. This is the case for the human cytomegalovirus exon 1 protein and viral mitochondrialocalized inhibitor of apoptosis (Bozidis et al 2010, Zhang et al 2011, for the hepatitis C virus core protein (Williamson & Colberg-Poley 2009, Horner et al 2011, 2015, for the human immunodeficiency virus protein-R (Huang et al 2012) and for the dengue virus (Chatel-Chaix et al 2016).…”
Section: Er-mitochondria Miscommunication and Other Diseases Associatmentioning
confidence: 99%